Incidence and Predictors of Hand-Arm Musculoskeletal Complaints among Vibration-exposed African Cassava and Corn Millers - Lukuke Hendrick Mbutshu; Kaj Francoise Malonga; Nlandu Roger Ngatu; Sakiko Kanbara; Benjamin Longo-Mbenza; Narufumi Suganuma (Elsevier, 2014)
Background: Cassava and corn milling is a growing small-scale enterprise in Africa. We aimed to determine the incidence of hand-arm musculoskeletal complaints among vibration-exposed Congolese cassava and corn millers in the previous 12 months. Methods: A cross-sectional study was conducted, prior to a follow-up study, from March to May 2013 among cassava/corn millers in Lubumbashi, Democratic Republic of Congo, in which 365 millers age-matched to 365 civil workers anonymously answered a questionnaire. Results: Overall incidence of hand-arm musculoskeletal complaints was 25.8% in millers (vs. 5.2% in civil workers; p < 0.001). The risk of experiencing musculoskeletal symptoms was seven times higher in millers [vs. civil workers; odds ratio (OR) = 7.10; 95% confidence interval (CI): 4.03-12.50; p < 0.0001]; 2.4 times higher in smoking millers (vs. smoking civil office workers; OR = 2.36; 95% CI: 1.42-3.88; p < 0.001); 3.6 times higher in millers with longer daily exposure (> 8 hours; vs. those working ≤ 8 hours; OR = 3.56; 95% CI: 1.93-3.61; p = 0.026); and 7.4 times higher in young millers (vs. older millers, OR = 7.39; 95% CI: 1.29-75.52; p < 0.001). Smoking, number of cigarettes, and daily exposure duration were positively correlated with musculoskeletal complaints. Conclusion: This study revealed a relatively high incidence of musculoskeletal complaints among African cassava and corn millers. The use of anti-vibration protective equipment and the regulation of this hazardous occupation may reduce the burden of musculoskeletal disorders in millers.